PENGARUH CUSTOMER RELATIONSHIP MARKETING DAN NILAI NASABAH TERHADAP LOYALITAS NASABAH PERBANKAN (STUDI PT. BNI CABANG TEMBILAHAN DI KOTA TEMBILAHAN ) - Santosa, Harry; Karneli, Okta (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
This research aims to determine the influence of customer relationship marketing and customer value towards the loyalty of banking customer (case study PT. BNI branch Tembilahan in Tembilahan City). Customer relationship marketing as variable x1, customer value as variable x2 and the loyalty of banking customer as variable y. The research method in this research is quantitative method with SPSS programme, which the sample is the banking customers as much as 50 respondents. As (Roscoe, 2009) stated that the decent size in a research is between 30 to 500. The sample in this research is 50 customers of PT. BNI branch Tembilahan which is enough to represent the population. The data is collected through the questionnaires.The results of this research concludes that the variable of customer relationship marketing is significantly influential to the banking customer and the customer value is significantly influential to the loyalty of banking customerKeywords: Customer Relationship Marketing, Customer Value and Customer Loyalty Banking